Early Detection of Patients at Risk of Developing a Post-Traumatic Stress Disorder After an ICU Stay*. Issue 11 (November 2020) - Wawer, Emilie; Viprey, Marie; Floccard, Bernard; Saoud, Mohamed; Subtil, Fabien; Wafa, Hashim; Rheims, Elodie; Rimmelé, Thomas; Poulet, Emmanuel
Abstract : Objectives: To evaluate the diagnostic accuracy of the Impact Event Scale-Revisited assessed following ICU discharge to predict the emergence of post-traumatic stress disorder symptoms at 3 months. Design: Prospective cohort study. Setting: Three medical or surgical ICU of a French university hospital (Lyon, France). Patients: Patients greater than or equal to 18 years old, leaving ICU after greater than or equal to 2 nights of stay, between September 2017 and April 2018. Interventions: Patients completed the Impact Event Scale-Revisited and the Peritraumatic Dissociative Experiences Questionnaire within 8 days after ICU discharge and the Impact Event Scale-Revisited again at 3 months by phone. Patients having an Impact Event Scale-Revisited greater than or equal to 35 at 3 months were considered as having post-traumatic stress disorder symptoms. Measurements and Main Results: Among the 208 patients screened, 174 were included and 145 reassessed by phone at 3 months. Among the patients included at baseline, 43% presented symptoms of acute stress. At 3 months, 13% had an Impact Event Scale-Revisited greater than or equal to 35 and 17% had a score between 12 and 34. Regarding the performance of the Impact Event Scale-Revisited performed within 8 days after the ICU discharge to predict post-traumatic stress disorder symptoms at 3 months, the area under the curve was 0.90 (95% CI, 0.80–0.99), and an Impact Event Scale-Revisited greater than or equal to 12 had a sensitivity of 90%, a specificity of 71%, a positive predictive value of 32%, and a negative predictive value of 98%. History of anxiety disorder odds ratio = 3.7 (95% CI, 1.24–11.05; p = 0.02) and Impact Event Scale-Revisited greater than or equal to 12 odds ratio = 16.57 (95% CI, 3.59–76.46; p < 0.001) were identified as risk factors for post-traumatic stress disorder symptoms. Conclusions: Impact Event Scale-Revisited assessed at ICU discharge has a good ability for the detection of patients at risk of developing post-traumatic stress disorder symptoms. Patients with history of anxiety disorder and those presenting acute stress symptoms at ICU discharge are more at risk to develop post-traumatic stress disorder symptoms.